Implikasi Keberadaan Spesies Invasif Eceng Gondok Terhadap Komunitas Serangga Parasitoid - Sapdi Sapdi (Jurnal Agrista, 2009)
Implications of the Existance of Invasive Species-Waterhyacinth on Communities of Parasitoid InsectABSTRACT. The introduction of an invasive exotic plant species may influence parasitoid insect community indirectly. The objective of this research is to evaluate the implication of the existence of invasive species-waterhyacinth on parasitoid insect community. The research was done in several fresh water ecosystem occupied by waterhyacinth in west java and DKI Jakarta, conducted during January 2004 to March 2006. Sweep net and yellow pan trap were use to collect the sample of insects. The result of the research showed that the existence of waterhyacinth may indirectly resulted in decreasing species richness and diversity of parasitoid insect. The observation also showed that the existence of waterhyacinth may lead to homogenization of parasitoid insect in aquatic vegetation.